Overview Of Nurse's Knowledge About Nosocomial Infection: Literature Review - Andan Firmansyah; Lilis Lismayanti; Deni Kurniawan (Jurnal Vocational Nursing Sciences (VNUS), 2020)
Background: Nosocomial infections or also known as hospital-acquired infections occur in patients who are hospitalized for at least 72 hours and these patients do not show symptoms of infection when admitted to the hospital. Nurses can take actions that result in nosocomial infections if they have poor knowledge about nosocomial infections. Objective: This study aims to describe the knowledge of nurses about nosocomial infections. Methods: The method is a literature review by searching sourced from an electronic database including Google Scholar and DOAJ from 2014-2019 using 15 journals related to the description of nurses' knowledge about nosocomial infections. Results: The results of the literature review showed that there were 8 articles on good knowledge of nurses, 6 with sufficient knowledge, and 1 article with less knowledge. Conclusion: Knowledge of a good nurse can be influenced by several factors including Age, length of work, level of education and training followed. Because good knowledge of nurses can prevent nosocomial infections.